(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the role of knowledge management in enhancing the competitive advantage of Sabratha University from the perspective of its faculty members. The study employed a descriptive-analytical survey methodology. The study population consisted of all faculty members at Sabratha University, totaling 45 individuals. A survey sample of 45 individuals was used to gather data from this population. A questionnaire was developed and distributed to the sample. The study yielded several key findings, including: the degree of knowledge management implementation and the level of competitive advantage at Sabratha University, as perceived by faculty members, were moderate; knowledge management has a strong impact on achieving competitive advantage at the university; and the study recommends fostering a culture that encourages knowledge generation and sharing within the university, providing sufficient financial resources to support researchers and innovators in producing knowledge and creating a suitable environment for them, and aligning university programs and colleges with quality standards and academic accreditation to achieve competitive advantage.